Marhaenisme sebagai Rekontekstualisasi Marxisme dalam Pemikiran Sukarno - Muslim, Fauzian Aulia; Rochwulaningsih, Yety; Sudarsih, Sri (Department of History, Faculty of Humanities, Diponegoro University, 2025)
This study aims to analyze Marhaenism as an ideology of struggle for marginalized groups that emerged from a process of dialectical engagement and recontextualization of Sukarno’s thought in relation to Marxism within the Indonesian context. The research employs the historical method, consisting of heuristic research, source criticism, interpretation, and historiography. The findings demonstrate that Marhaenism adopts the concept of class analysis from Marxism, yet does not apply it in a dogmatic manner. Sukarno reflected on the material conditions of Indonesian society, which differed significantly from the European context, where the oppressed class largely consisted of proletarians who did not own the means of production. In contrast, oppressed classes in Indonesia encompassed a broad spectrum of social groups, ranging from those without means of production to small-scale owners of productive assets. Sukarno referred to this oppressed class as the “Marhaen,” which included peasants, fishermen, small traders, and workers. Through this process of recontextualization, Sukarno developed distinctive concepts such as the Marhaen social class, Socio-Nationalism, and Socio-Democracy as an ideological framework of struggle suited to Indonesia’s social realities. This study therefore argues that Marhaenism represents a creative adaptation of Marxism rooted in the historical and social conditions of Indonesian society, offering an alternative ideology of emancipation for marginalized groups beyond the framework of orthodox Marxism.